2019
DOI: 10.1177/0040563919856610
|View full text |Cite
|
Sign up to set email alerts
|

The Catholic Sexual Abuse Crisis as a Theological Crisis: Emerging Issues

Abstract: The sexual abuse crisis has long-term consequences: not only on the victims and survivors of abuse, but also on the theological standing and balance of the Catholic Church throughout the world. Theological rethinking in light of the abuse crisis is necessary: not only from the lens of those who have suffered, but also from the lens of the changes caused by this global crisis in the history of the whole Catholic community. The article examines the consequences of the abuse crisis on different theological discip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
1
0
4
Order By: Relevance
“…Some empirical evidence collected by journalists and scholars shows that several members of the clergy do not follow the strict rules of sexual continence that they pretend to impose on the laity (Marzano 2021). Historians have also revealed that abuse is not a modern phenomenon and existed in the past, although, due to a lack of archives and testimonies, its prevalence cannot be objectively evaluated (Faggioli 2019). Truly enough, some of the quantitative results have been criticized by specialists.…”
Section: Catholic Church: Sexual Abuse and Accountability/democracymentioning
confidence: 99%
“…Some empirical evidence collected by journalists and scholars shows that several members of the clergy do not follow the strict rules of sexual continence that they pretend to impose on the laity (Marzano 2021). Historians have also revealed that abuse is not a modern phenomenon and existed in the past, although, due to a lack of archives and testimonies, its prevalence cannot be objectively evaluated (Faggioli 2019). Truly enough, some of the quantitative results have been criticized by specialists.…”
Section: Catholic Church: Sexual Abuse and Accountability/democracymentioning
confidence: 99%
“…Las investigaciones sobre los abusos llevadas adelante desde la Iglesia, las congregaciones religiosas, los Estados y los organismos independientes ya conforman un abultado cuerpo científico que impiden mirar hacia otro lado, y obligan a abrir una discusión sobre las personalidades carismáticas y sus comunidades en la Iglesia Católica, dadas las condiciones particulares favorables al abuso creado por algunos modos de configurarse de las nuevas realidades eclesiales 53 .…”
Section: Iglesiaunclassified
“…Hasta ahora los nuevos movimientos y comunidades eclesiales no formaron parte de la conversación sobre la crisis mundial de abuso y no se han interesado por la reforma institucional, cuestión inevitable que dejan planteados los análisis sobre la crisis de los abusos 54 .…”
Section: Iglesiaunclassified
“…En definitiva, la crisis producida por las continuas revelaciones de abusos sexuales es uno de los mayores desafíos que debe enfrentar la Iglesia en el presente y en el futuro. Los problemas desnudados por la crisis de abusos son un signo de los tiempos con los cuales debemos dialogar teológica y pastoralmente (Faggioli, 2019), proponiendo respuestas institucionales de remediación y reforma en la comunidad eclesial (Schickendantz, 2019). En reiteradas ocasiones, la idealización de las figuras carismáticas ha fomentado culturas organizacionales de una "obediencia deferente", en que la persona condesciende al dictamen ajeno, sin querer sostener el suyo (Lennan, 2019).…”
Section: Tensiones En La Iglesia Frente a Las Propuestas De Renovaciónunclassified